Augmented Reality Flashcard Prototype Design as an Instructional Medium for Introducing West Java Traditional Houses in Elementary School - Siti Nuraisyah; Sumardi Sumardi; Rosarina Giyartini; Muhammad Rijal Wahid Muharram (Universitas Pendidikan Indonesia (UPI), 2021)
Social Studies is a subject which contains topics about Indonesian traditional houses. Instuructional media for introducing traditional houses that are generally used in elementary schools are limited to video, 2-dimensional images, and textbooks. The use of media that is less varied results in students become bored. The use of technology in the field of education is increasing diverse which can make it easier for teachers and students to convey and receive the information. Augmented Reality is one of the technologies that can be used as an alternative to traditional house instructional media because it can display real traditional houses in 3 dimensions. This study aims to describe the design of an Augmented Reality flashcard prototype as a learning medium for West Java traditional houses in elementary schools. The method used was Design-Based Research which has four stages. This research was carried out until the second stage, namely developing product prototypes based on existing theories, design principles, and technological innovations. The result of this research is a flashcard prototype design and Augmented Reality application. The flashcards had two sides that were used as markers to bring up Augmented Reality objects. The Augmented Reality application was designed to have two main menus, each of which serveed to display a real West Java traditional house in the form of a three-dimensional object and displays a traditional house that can be seen from various sides or points of view. This application was also equipped with supporting features, such as complete information, sound, scale, rotation, and other features.